From access to agency: exploring the synergy of openness, inclusion, and equity in education - Alvarez-Icaza, Inés; Martínez-Briones, Benito Javier; Antón-Ares, Paloma; Saavedra-López, Ana María (Frontiers in Education, 2025)
Open education has emerged as a promising approach to addressing persistent disparities in access to learning and knowledge creation. When thoughtfully aligned with principles of inclusion and equity, it offers meaningful possibilities for shaping more just and responsive educational environments. Yet such alignment is neither automatic nor guaranteed. While Open Educational Resources can extend the reach of education, they may also inadvertently reinforce structural inequalities if not designed with sufficient attention to accessibility, learner diversity, and contextual relevance. This study draws on a participatory consultation conducted during the 2025 Open Education Week in connection with the UNESCO Open Education Fellowship. Educators and researchers reflected on priority areas for advancing inclusion and equity within the open education movement. Their responses underscored the urgency of improving support for neurodiverse learners, advancing adaptive learning strategies, and addressing the needs of marginalized communities. These insights served as a point of departure for a broader discussion on inclusive pedagogical design, with particular attention to integrating evidence-based learning techniques and frameworks. Efforts to embed inclusion and equity into open education demand more than the availability of resources. They require ongoing pedagogical reflection, intentional design, and institutional support for those historically underserved by educational systems. As emphasized by the Dubai Declaration, openness becomes meaningful when it is grounded in shared responsibility and enacted through concrete practices. The reflections gathered here aim to contribute to that effort, pointing to practical considerations for fostering learning environments that are more inclusive, adaptive, and attentive to diverse learner realities.